2005
DOI: 10.1111/j.1600-0501.2005.01096.x
|View full text |Cite
|
Sign up to set email alerts
|

Zygoma implant‐supported midfacial prosthetic rehabilitation: a 4‐year follow‐up study including assessment of quality of life

Abstract: Zygoma implants can reliably anchor the midfacial maxillary prostheses and enable a quality of life comparable with autologous maxillary reconstruction. They can be replaced immediately if local infection or loosening should occur. A premolar and canine position reduce leverage when no anterior alveolar process is present. The patient can alternatively be provided with dental implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
45
1
8

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 38 publications
0
45
1
8
Order By: Relevance
“…Recent investigations have confirmed the effectiveness of obturator prostheses in terms of speech, masticatory function, swallowing and appearance, 5,28 especially for small defects. 6,12 There is evidence that speech can be restored to a preoperative level with a maxillary obturator prosthesis.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Recent investigations have confirmed the effectiveness of obturator prostheses in terms of speech, masticatory function, swallowing and appearance, 5,28 especially for small defects. 6,12 There is evidence that speech can be restored to a preoperative level with a maxillary obturator prosthesis.…”
Section: Discussionmentioning
confidence: 98%
“…36 Since then several reports have been published on the clinical performance of zygoma implants. 28,29,31,35,[37][38][39][40][41][42][43][44][45][46] The 2 primary indications for the use of zygoma implants are atrophic edentulous maxillae and defects after maxillary resection. 28,29,40 Zygoma implants are generally placed at a 30 to 60-degree angle relative to the occlusal plane.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some examples of late complication are: loss of fixation or osseointegration, bucco sinusal communication, fenestration of the buccal mucosa, chronic sinusitis and sinus pathologies, palatal emergency of fixations, mucositis and peri-implantitis. (6)(7)(8)(9)(10)(11)(12)(13)(14) Recent systematic review studies reported the survival and presence of complications related of zygomatic fixation. (15) They conclude that the studies with a high level of evidence are scarce.…”
mentioning
confidence: 99%